THE RELATIONSHIP BETWEEN CONFORNITY AND HEDONIC LIFESTYLE IN STUDENTS - Hernu, Rahmi; Aulia, Farah (In Trend : International Journal of Trends in Global Psychological Science and Education, 2023)
Current developments and modernization are increasing and greatly influencing a person's lifestyle. This research aims to determine the relationship between conformity and hedonic lifestyle in students. This research uses quantitative methods with a correlational approach. The subjects in this research were 272 Padang City students who met the criteria set using a purposive sampling technique. The data collection method in this research uses a hedonic lifestyle scale with a reliability of 0.942 and a conformity scale with a reliability of 0.942. Data analysis uses product moment correlation with the help of the Statistical Package for Sciences (SPSS) 26.0 for Windows program to obtain hypothesis test results with a value of r = 0.372 with a significance value of p = 0.00 (p<0.05). This shows that there is a significant positive relationship between conformity and the hedonic lifestyle of Padang City students, meaning that the higher the student's conformity, the higher the hedonic lifestyle carried out by the student. Overall, the results show that the majority of Padang City students have a moderate conformity and hedonic lifestyle.